Comparative Analysis of Antiglycation Capacity of Aqueous and Methanolic Extracts of Vegetables (Global Journal of Medical Research, 2014)
Glycation is a reaction between amino group of blood proteins and reducing sugars in vitro conditions which are involved in a number of pathologies and disease states including Alzheimer's and diabetes. Equal concentration of different inhibitor extracts (sweet potato, turnip and methi) and glucose were used. Eight combinations of each extract were made and all these were placed at 37oC for five weeks incubation. Human normal plasma was used as a protein source. Glycation was analyzed by Thiobarbituric acid (TBA) technique which results that aqueous and methanol extracts of sweet potato and turnip showed no inhibition of nonenzymatic glycation but act as activator of reaction while aqueous extract of methi showed maximum inhibition of non-enzymatic glycation in 5th week of incubation and for methanol extract inhibition was maximum in 3rd week of incubation. In all extracts of three vegetables, extracts of methi were more effective against non-enzymatic glycation. These findings suggest that in future methi can be used for lowering glucose level in the body as it is efficient in lowering the glycation level in different conditions when level of glucose is high.